EFFICIENCY AND SAFETY OF MELATONIN ADMINISTRATION IN THE PATIENTS WITH ATOPIC DERMATITIS - V. S. Shirinsky; V. M. Nepomnyashikh; M. I. Leonova; O. L. Krugleeva; V. S. Kozhevnikov; N. Yu. Solovyova; A. V. Shurlygina; G. I. Litvinenko; I. V. Shirinsky; O. A. Malysheva (Медицинская иммунология)
Abstract. The objective of this study was to determine efficacy and safety of melatonin administered in addition to conventional atopic dermatitis treatment. Study design: open randomized parallel group study. Patients and treatment: Forty-six patients with exacerbation of moderate-to-severe atopic dermatitis were included into the study. The patients were randomized, to receive either complex conventional treatment, or conventional treatment plus melatonin at a daily dose of 3 mg, being administered at 9 P.M. Primary endpoint of the study: Severity scoring using SCORAD index. Assessment of pharmacological effects included counting functional evaluation of T-cells, B-cells and phagocytes, as well as morning and evening serum levels of IgE, IL-4 and IFN-γ. Results. In melatonin group, a statistically significant SCORAD index reduction was revealed, as compared with conventionally treated group (84% vs 60%). Addition of melatonin to conventional treatment caused a 63 per cent decrease in relative risks of unfavorable outcome, defined as absence of 20 per cent improvement by the SCORAD scale. Clinical improvement in melatonin group was associated with increase in CD8+cell counts, IgM levels and indices of Fc-dependent monocyte and neutrophil phagocytosis. Circulating IgE and IL-4 levels did significantly decrease. In melatonin group, there were significant differences between the morning and evening counts of CD3+, CD4+, CD8+, CD16+ cells, like as levels of circulating IFN-γ. These preliminary data suggest efficacy of melatonin administration in the patients with atopic dermatitis. Further research is needed to confirm these results.